(untitled) (Quaestiones Disputatae: temas en debate, 2016)
The article considers the importance of the concept dignity to understand some problems of exclusion brought by inequality. The most common ones are the ones related to labor exploitation where children live for their non citizen condition. The main point of the work state that whatever is done to get peace culture , it is necessary first to guarantee the principle of dignity to all members without ambiguity. This means first to revise the criteria through which the citizen, person, worker or work conception was made. This is because the current definitions admit different interpretations which might violate children rights. The article refers to three main aspects of the problem: a) the context where the labor exploitation of children in Mexico. B) some points related to the most important definitions around children work c) a philosophical thought as from the idea of dignity of Kant, the vulnerability of children who work.